Dental Hygienists’ Awareness of Medication-Related Osteonecrosis of the Jaw in Private Dental Clinics in Japan - Yosuke Iijima DDS, PhD; Miki Yamada DDS; Mai Amano MS; Saya Watanabe MS; Miki Fujimaru BS; Ayako Uematsu BS; Shunsuke Hino DDS, PhD; Motohiko Sano PhD; Norio Horie DDS, PhD; Hiroshi Sakagami PhD; Takahiro Kaneko DDS, PhD (Gerontology and Geriatric Medicine)
Purpose: Medication-related osteonecrosis of the jaw (MRONJ) caused by bisphosphonates (BPs) and denosumab (Dmab) is still a major oral adverse event caused by cancer treatment and may be under-recognized by private dental services. With the aim of reducing the prevalence of MRONJ, this study, which is a pilot study for a planned future large-scale survey, compared knowledge about MRONJ between dental hygienists (DHs) in private dental clinics and those in cancer center hospitals. Methods: We conducted a questionnaire-based survey regarding MRONJ between 1 November 2023 and 31 January 2024 on DHs at a cancer base hospital and a private clinic in Saitama, Japan. We statistically analyzed the data collected using the χ 2 test or Fisher’s exact test with the level of significance set at 5%. Results: This study included 10 in-hospital and 53 private clinic DHs. The in-hospital DHs had appropriate knowledge of MRONJ. However, compared with the in-hospital DHs, although the private clinic DHs knew that BPs are used for osteoporosis, significantly fewer had knowledge of Dmab ( p  < .001) or knew that BPs and Dmab could also be used to treat cancer (both p  < .001). In addition, few private clinic DHs were aware of MRONJ cases refractory to antibiotic treatment alone ( p  = .012). Conclusion: These findings suggest that private clinic DHs have less knowledge of MRONJ than those in cancer base hospitals.